Fishing gear–related injuries and mortality of seabirds in coastal northern Argentina - Beron, Maria Paula (2021)
Worldwide, many seabirds are killed annually when they become entangled in gear used in coastal fisheries. This includes seabirds along the coast of Argentina, where recreational fishing occurs year-round and where little attention has been paid to the issue. We report here results for a study conducted in the vicinity of Mar del Plata Harbor and Mar Chiquita Lagoon in Buenos Aires Province, Argentina, during the non-breeding season (March-September 2016). We found and inspected 46 individuals of ten species with moderate (30%), severe (46%), and lethal (24%) lesions from fishing gear entanglement. Coastal birds (83%) dominated the tally, with gulls being the most affected group. The species with the most frequent occurrence in Mar del Plata Harbor and Mar Chiquita Lagoon were Olrog's Gull Larus atlanticus (17.1% and 7.9%, respectively), followed by Kelp Gull L. dominicanus (1.3% and 0.3%, respectively). Among Olrog's Gulls, adults were found most frequently in the Mar del Plata Harbor, whereas sub-adults were more frequent at Mar Chiquita Lagoon. We recommend persistent monitoring to improve understanding of interactions between seabirds and both artisanal and sport-recreational fisheries, as well as campaigns to promote awareness of the issue within the fishing community. The responsible removal of discarded fishing tackle must be encouraged in coastal areas.